INVESTIGATION OF THE EFFECT OF SHEAR THICKENING FLUID AND FABRIC STRUCTURE ON INTER-YARN FRICTION PROPERTIES IN TWARON FABRICS - Yanen, Cenk; Solmaz, Murat Yavuz; Aydoğmuş, Ercan (My University, 2020)
It is known that shear thickening fluids increase the energy absorption capacity of high performance fabrics. For this reason, soft body armors have been produced by impregnating shear thickening fluids recently on high performance fabrics. In this study, it is aimed to examine the effects of shear thickening fluid and fabric structure on the inter-yarn friction properties of para-aramid fabrics with different properties. Fumed silica was dispersed in polyethylene glycol to produce shear thickening fluid. Twaron 200 and Twaron 460 para-aramid fabrics with different properties such as threads number (105x105 and 67x67), areal density (200 gr / $m^2$ and 460 gr / $m^2$) andlinear density (930 and 3360 Dtex) were impregnated with shear thickening fluid. It was observed that both of shear thickening fluid impregnated fabrics had higher yarn pull-out force than neat fabrics due to inter-yarn friction. When shear thickening fluid impregnated fabrics are according to maximum yarn pull-out force; Twaron 200 and Twaron 460 fabrics requires approximately 3 times and 9 times more force to pull-out the yarn in comparison to the neat fabric respectively. In this study, it has been observed that the positive effects of shear thickening fluid impregnation on energy absorption of Twaron fabrics depend on structural parameters such as threads number, areal density and linear density.
Keywords: Malzeme Bilimleri; Tekstil